2021
DOI: 10.1093/neuros/nyab257
|View full text |Cite
|
Sign up to set email alerts
|

A Crowdsourced Consensus on Supratotal Resection Versus Gross Total Resection for Anatomically Distinct Primary Glioblastoma

Abstract: BACKGROUND Gross total resection (GTR) of contrast-enhancing tumor is associated with increased survival in primary glioblastoma. Recently, there has been increasing interest in performing supratotal resections (SpTRs) for glioblastoma. OBJECTIVE To address the published results, which have varied in part due to lack of consensus on the definition and appropriate use of SpTR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Most neurosurgeons surveyed (n=57, 80.3%) agree or strongly agree that GTR plus resection of any noncontrast enhanced disease is an appropriate de nition for SpTR (Table 2A). Compared to the cohort of expert neurosurgical oncologists who previously provided their opinions on this de nition, a two proportion z-test demonstrated that a similar fraction agreed or strongly agreed that it was tting (Experts: n=18, 85.7%; Tumor Section: n=57, 80.3%; p=0.575) [33]. GTR plus resection 1-2 cm beyond contrast-enhancing disease was the second most commonly endorsed de nition, with 52 (73.2%) neurosurgeons agreeing or strongly agreeing with this de nition of SpTR.…”
Section: De Nitions Of Sptr and Eloquencementioning
confidence: 99%
See 1 more Smart Citation
“…Most neurosurgeons surveyed (n=57, 80.3%) agree or strongly agree that GTR plus resection of any noncontrast enhanced disease is an appropriate de nition for SpTR (Table 2A). Compared to the cohort of expert neurosurgical oncologists who previously provided their opinions on this de nition, a two proportion z-test demonstrated that a similar fraction agreed or strongly agreed that it was tting (Experts: n=18, 85.7%; Tumor Section: n=57, 80.3%; p=0.575) [33]. GTR plus resection 1-2 cm beyond contrast-enhancing disease was the second most commonly endorsed de nition, with 52 (73.2%) neurosurgeons agreeing or strongly agreeing with this de nition of SpTR.…”
Section: De Nitions Of Sptr and Eloquencementioning
confidence: 99%
“…For each of the ten anatomically distinct GBM cases, survey respondents reviewed MR images and categorized the eloquence of the tumor's location, indicated whether it would be reasonable to randomize it to SpTR or GTR, and identi ed their personal treatment plan and any adjunct perioperative techniques they would use (Supplement). Consensus on each case's eloquence, equipoise, or treatment plan was de ned as at least 70% agreement among the respondents, following past conventions [32,33].…”
Section: Survey Distribution and Data Collectionmentioning
confidence: 99%
“…Other surgical techniques, such as awake craniotomy with cortico-subcortical mapping and neuronavigational systems also play a critical role in appropriately selected cases thereby preserving neurologic function and bettering patient outcomes [ 62 , 71 , 72 ]. Some have also advocated for a supratotal resection for GBM [ 73 ].…”
Section: Treatment Overviewmentioning
confidence: 99%
“…Several studies have shown the association between GBM preoperative magnetic resonance imaging (MRI) features and patients prognosis, but only a fraction of them have focused on imaging configuration of PBZ (Al‐Holou et al, 2020; Khalafallah et al, 2021; Molinaro et al, 2020). Moreover, the radiological identification of PBZ, intended as the normal brain tissue bordering the tumor, is problematic.…”
Section: Translational Aspectsmentioning
confidence: 99%
“…One of the concerns of the resection of the FLAIR peritumoral hyperintensities is the amount of the region that need to be resected to increase the patient OS because of studies reporting contradictory results (Certo et al, 2019; Molinaro et al, 2020; Vivas‐Buitrago et al, 2022). In addition, some authors consider some anatomical locations more suitable for supramarginal resection than others (Khalafallah et al, 2021). Among authors supporting resection of NE area in GBMs, some suggest that NE region resection should be not more than 60%, whereas other suggest to resect as much as possible (Molinaro et al, 2020; Pessina et al, 2017; Vivas‐Buitrago et al, 2022).…”
Section: Translational Aspectsmentioning
confidence: 99%